2007
DOI: 10.1007/s00395-007-0689-5
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β receptor antagonism attenuates myocardial fibrosis in mice with cardiac-restricted overexpression of tumor necrosis factor

Abstract: The mechanisms that are responsible for the development of myocardial fibrosis in the inflammatory cardiomyopathy are unknown. Previously we have generated lines of transgenic mice with cardiac restricted overexpression of tumor necrosis factor (MHCsTNF mice), a proinflammatory cytokine. The MHCsTNF mice develop a heart failure phenotype that is characterized by progressive myocardial fibrosis, as well as increase levels transforming growth factor-β (TGF-β) mRNA and protein. In order to determine whether TGF-β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 37 publications
2
49
1
2
Order By: Relevance
“…In the present study, MMP-2 activity was, however, similar amongst all groups, which diverges from a previous study where reduced MMP-2 activity was responsible for the ECM changes observed STZ-rats with the same duration of diabetes [45]. It is currently accepted that MMP-2 activity is inhibited by TIMP-2 and its expression increased by TGF-b1 signalling, via Smad 7 [45] and Smad 2/3 activation [36]. In our study we found a tendency for both TIMP-2 and TGF-b 1 to increase.…”
Section: Effects Of Diabetes Mellituscontrasting
confidence: 56%
“…In the present study, MMP-2 activity was, however, similar amongst all groups, which diverges from a previous study where reduced MMP-2 activity was responsible for the ECM changes observed STZ-rats with the same duration of diabetes [45]. It is currently accepted that MMP-2 activity is inhibited by TIMP-2 and its expression increased by TGF-b1 signalling, via Smad 7 [45] and Smad 2/3 activation [36]. In our study we found a tendency for both TIMP-2 and TGF-b 1 to increase.…”
Section: Effects Of Diabetes Mellituscontrasting
confidence: 56%
“…The effects of the oral TGF␤RI antagonist NP-40208 on transgenic mice with cardiac-restricted overexpression of tumor necrosis factor (MHCsTNF) have also been examined (30). MHCsTNF mice develop a heart failure phenotype characterized by progressive myocardial fibrosis, an increase in TGF-␤ levels, and LV diastolic dysfunction as shown by an increase in the chamber stiffness constant using the Langendorff method.…”
Section: Discussionmentioning
confidence: 99%
“…These authors reported that TGF-b1 upregulated NOX4 expression and promoted the conversion of fibroblasts to myofibroblasts, which are the main producers of collagen in the extracellular matrix. This study implied that NOX4 may be responsible for driving cardiac fibrosis in response to TGFb1 stimulation, the latter being well established as a driver of cardiac fibrosis [46]. However, TGF-b may also have beneficial actions as evidenced by data that TGF-b inhibition is detrimental in mice after MI [47].…”
Section: Interstitial Cardiac Fibrosismentioning
confidence: 94%